2015
DOI: 10.1016/j.jpha.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and supported liquid extraction methods for the determination of sitagliptin and simvastatin in rat plasma by LC–ESI–MS/MS

Abstract: Three extraction methods were compared for their efficiency to analyze sitagliptin and simvastatin in rat plasma by LC–MS/MS, including (1) liquid–liquid extraction (LLE), (2) solid phase extraction (SPE) and (3) supported liquid extraction (SLE). Comparison of recoveries of analytes with different extraction methods revealed that SLE was the best extraction method. The detection was facilitated with ion trap-mass spectrometer by multiple reactions monitoring (MRM) in a positive ion mode with ESI. The transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The high selectivity and minimal matrix effects observed with this method could in part be attributed to the high retention capacity of GDC‐0425 on the C 18 column described earlier. SLE proved to be an efficient alternative to traditional LLE (Pirard et al, ; Ramesh et al, ). SLE played an important role in removing unwanted components in the sample matrix while ensuring high selectivity and minimal matrix effects with this method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high selectivity and minimal matrix effects observed with this method could in part be attributed to the high retention capacity of GDC‐0425 on the C 18 column described earlier. SLE proved to be an efficient alternative to traditional LLE (Pirard et al, ; Ramesh et al, ). SLE played an important role in removing unwanted components in the sample matrix while ensuring high selectivity and minimal matrix effects with this method.…”
Section: Resultsmentioning
confidence: 99%
“…SLE also has advantages of avoiding emulsion formation and alleviating many of the liquid handling issues associated with traditional LLE in addition to being automation friendly (Pirard et al, ; Ramesh, Manjula, Bijargi, Sarma, & Sita Devi, ). Some studies also reported that extraction efficiency was improved significantly with SLE compared with SPE for the compounds tested and the SLE method seemed to combine the advantages of LLE and SPE (Ramesh et al, ; Breitenbucher, Arienti, & McClurel, ). In this work, we tested protein precipitation extraction first and found out that the recovery was low.…”
Section: Methodsmentioning
confidence: 99%
“…The calibration standard solutions of blank plasma samples were prepared by spiking (5 mL) of drug‐free plasma provided by healthy volunteers with appropriate stock solutions of selected drugs. In order to eliminate the expected protein binding with both drugs in plasma samples (Kim et al, ; Ramesh et al, ), the procedure explained by (Hadjmohammadi & Ghambari, ) was implemented with some modifications. Methanol (7 mL) was added to 5 mL of spiked plasma samples and vortexed for 10 min followed by freezing at −20°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Simvastatin {SIV; [(1S,3R,7S,8S,8aR)‐8‐{2‐[(2R,4R)‐4‐hydroxy‐6‐oxooxan‐2‐yl]ethyl}‐3,7‐dimethyl‐1,2,3,7,8,8a‐hexahydronaphthalen‐1‐yl]‐2,2‐dimethylbutanoate} is an anticholesteremic and antilipidemic statin agent widely used in the treatment of hypercholesterolemia, dyslipidemia and coronary heart disease (Ramesh, Manjula, Bijargi, Sarma, & SitaDevi, ). After oral administration, SIV as a semisynthetic analog of lovastatin is rapidly absorbed (time to peak concentration 1–2 h) from the gastrointestinal tract and hydrolyzed to its active β ‐hydroxyl acid (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many efforts have been invested in the development of novel sitagliptin formulations, such as longer-acting formulation [7][8][9]. Correspondingly, analytic methods have been emerged for analyzing sitagliptin in biological matrixes (Table 1), such as RPLC [10][11][12], GC-MS/MS [13], and LC-MS/MS [14][15][16][17]. Among them, the hydrophilic interaction DART is a kind of ambient ionization technique, by which analytes will be ionized by reacting with the inert gases or water molecules of the excited-state under atmospheric pressure (Formula S1) [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%